Study of virulence factors in coagulase-negative staphylococci isolated from newborns - Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (2006)
Coagulase-negative staphylococci (CNS) have been identified as the etiological agent in various infections and are currently the microorganisms most frequently isolated in nosocomial infections. However, little is known about the virulence factors produced by CNS that contribute to the pathogenesis of infections caused by these microorganisms. The study of CNS isolated from infectious processes of newborns hospitalized in the Neonatal Unit of the Hospital of the Botucatu Medical School, Unesp, indicated Staphylococcus epidermidis as the most frequently isolated species (77.8%), which was also associated with clinically significant situations. The analysis of virulence factors revealed the production of slime in 20 (17.1%) of all CNS samples isolated and the synthesis of a broad spectrum of enzymes and toxins, including hemolysins (19.6%), lipase (17.1%), lecithinase (3.4%), DNAse (15.4%), thermonuclease (7.7%), and enterotoxin A, B or C (37.6%). Taking into consideration that the etiological importance of CNS has often been neglected, the present investigation confirmed that these microorganisms should not be ignored or classified as mere contaminants.